Resource utilization in village ecosystem of temperate zone of Garhwal Himalaya - Sharma, C.M.; Gairola, Sumeet; Kumar, Munesh; Rawat, Y.S.; Bagwari, H.K. (Indian Journal of Agroforestry, 2020)
The present study was conducted in the Rudraprayag and Tehri districts of Garhwal Himalaya on five mid altitudinal villages to study the utilization of resources by the inhabitants and their effect on the village ecosystem. The investigation has revealed that the average fuel wood and fodder consumption in these villages was 2636 Qt/yr/village and 6736.6 kg/day/village, respectively. The maximum production of wheat (1506 kg/ha), mustard (260 kg/ha) and pulses (598 kg/ha) was observed for village Dhaulana, whereas maximum production of paddy (1375 kg/ha) for village Karokhi, barley (782 kg/ha) for village Chunnikhal and finger millet (1478 kg/ha) and barnyard millet (1028 kg/ha) for village Bhanigram. The rate of exploitation of forest resources was verified by vegetation analysis, where no regeneration has been recorded from all the adjacent forests close to agricultural fields of the selected villages. The total basal cover of the agroforestry tree species was highest (19.60 m2/ha) at village Dhaulana and lowest (7.225 m2/ha) at village Chunnikhal.